Catalytic Pyrolysis of Impregnated Citronella Biomass Using Boric Acid to Produce Furfural - Nasim, Muhammad; Setiadi, Setiadi (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Citronella oil residue is one of the abundant lignocellulosic biomass wastes which has the potential to be converted into useful products through pyrolysis process. One of the useful products that can be produced from this residue is furfural compounds. Previous research has shown that furfural can be produced through the pyrolysis mechanism of lignocellulosic biomass. However, the amount of furfural compounds obtained is still relatively low. Therefore, in this study a research is carried out regarding catalytic pyrolysis process through impregnation method of biomass using boric acid as catalyst to produce furfural compounds with variation of catalyst ratio (0, 0.1, 0.3) and pyrolysis temperature (450 oC, 500 oC, 550 oC) to determine the optimal conditions for furfural production. Using GC-MS analysis, results were obtained which indicated the role of boric acid impregnation in increasing and maximizing the yield of furfural products. The optimal conditions for furfural production were obtained at a pyrolysis temperature of 550 oC and the use of a boric acid catalyst with a ratio of 0.1, whereby the yield of furfural compounds by GCMS analysis was 19.17% area.